Review of the Mexican species of Erythmelus (Hymenoptera: Mymaridae), with description of two new species - Guzmán-Larralde, Adriana J.; Triapitsyn, Serguei V.; Huber, John T.; González-Hernández, Alejandro (Zootaxa, 2015)
The Mexican species of Erythmelus Enock (Hymenoptera: Mymaridae) are revised. A key to females of 13 species is provided in both English and Spanish. Two new taxa are described—E. maya Guzmán-Larralde & Triapitsyn, sp. n. and E. tigres Guzmán-Larralde & Triapitsyn, sp. n. Six species are newly recorded from Mexico—E. angustatus Ogloblin, E. cingulatus Ogloblin, E. clavatus Ogloblin, E. gracilis (Howard), E. nanus Dozier, and E. noeli (Dozier), besides new geographic records for E. miridiphagus Dozier, E. picinus (Girault), E. psallidis Gahan, and E. rex (Girault) which were previously known from the country.